(untitled) (Medico Legal Update, 2021)
Hormones, their receptors, and the associated signaling pathways make compelling drug targets because of their wide-ranging biological significance to study the role of asprosin in obese male patients with diabetic mellitus type II. ELISA method was used to assay asprosin and insulin. Blood was taken with drawn sample from 30 obese normal patients with age range (40-60) years, 30 diabetic patients with age range (40-60) years at duration of disease (1-5) years and 30 normal healthy patients. The mean difference between T2DM according to insulin % (23.8±0.6) was increased than the mean of IFG (17.7±1.0) (P 0.000). The mean difference between T2DM according to asprosin (122.1±21.8) was increased than the mean of IFG (51.4±2.7) (P 0.000).the mean differences between DM2 and IFG cases in different weight groups (Ob., Ow. and Nw) according to insulin was studied, the results showed that, there were significant differences in DM and IFG obese groups (G1 and G2) according to insulin (24.18±1.13, 15.56±0.66) P (0.00), however, there were significant differences between DM and IFG in Normal weight groups (G5 and G6) according to insulin (19.98±0.93, 11.12) P (0.00), while no significant differences between DM and IFG in Over weight groups (G3 and G4) according to insulin (27.22±0.34,28.56±1.59) P (0.42).The mean differences between diabetic mellitus type 2 and impaired fasting glucose cases in different weight groups (obese, over weight and normal weight) according to Asprosin were shown in Table (3), Figure (). The results showed that, there were significant differences between DM and IFG in obese groups (G1 and G2) according to Asprosin (307.42±8.4, 66.3±2.2) P (0.00), However, there were significant differences between DM and IFG in overweight groups (G3 and G4) according to Asprosin (28.3±0.5, 51.7±3.2) P (0.00) In addition to that, there were significant differences between DM and IFG in normal weight groups (G5 and G6) according to Asprosin (30.5±1.7, 21.2±1.6)